Hierarchical QAM and Inter-Layer FEC for Multi-View Video Plus Depth Format in Two-Way Relay Channels - Dongho You; Sung-Hoon Kim; Dong Ho Kim (Applied Sciences)
This paper presents an enhanced method for the transmission of 3D video in the Multi-view Video plus Depth (MVD) format over Two-Way Relay Channels (TWRC). Our approach addresses the unique challenges of MVD-based 3D video by combining Hierarchical Quadrature Amplitude Modulation (HQAM), a method that prioritizes data layers based on importance, and Inter-Layer Forward Error Correction (IL-FEC), which protects critical data from errors. These are specifically designed to handle the dual-layer data structure where color data and depth information require different levels of error protection, and it reduces transmission errors and enhances the quality of MVD-based 3D video over TWRC. In the TWRC scenario, the proposed scheme optimizes transmission by reducing the number of relayed bitstreams by half while maintaining high-quality requirements, as demonstrated by significant improvements in the Structural Similarity Index (SSIM) for virtually synthesized views. Furthermore, we identify and optimize the hierarchical modulation parameter (<semantics>α</semantics>), which controls the priority and protection levels of different data streams. Systematically varying <semantics>α</semantics> reveals its substantial impact on the quality of the reconstructed 3D video, as measured by SSIM. Our results demonstrate that the proposed combination of HQAM and IL-FEC not only maintains the target SSIM of 0.9 for the virtually synthesized view under various relay conditions but also reveals the optimal <semantics>α</semantics> value for balancing the error protection between the color and depth map data streams. Notably, while increasing <semantics>α</semantics> enhances the protection of critical data (such as color video streams), it may concurrently degrade the quality of less important streams (like depth maps), highlighting the importance of fine-tuning <semantics>α</semantics> to achieve the best overall video quality. These findings suggest that our method provides a flexible and effective solution for high-quality 3D video transmission in challenging communication environments, potentially advancing the development of future 3D video delivery systems.